2015
DOI: 10.1016/j.egypro.2015.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Gas and Particulate Matter Products Formed in a Laminar Flow Reactor: Pyrolysis of Single-Component C2 Fuels

Abstract: Investigations that rank the tendencies of single-component fuels to form soot have given useful insights into how molecules and local molecular structure influences the conversion of carbon in fuel to soot. These studies can provide fundamental understanding of how functional group chemistry influences the products formed during pyrolysis or combustion. A series of experiments have been conducted which investigate the conversion of oxygenated and hydrocarbon C 2 molecules (ethanol, ethane, and ethylene) to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Thus, it is of great research and practical value to have a clear understanding of the soot formation mechanism. The formation process is known as a transition from the gas phase to the condensed phase, involving polycyclic aromatic hydrocarbons (PAHs) formation, nucleation, coagulation, surface growth, and aggregation, , which are influenced by many factors such as temperature, equivalence ratio (or carbon to oxygen (C/O) ratio), , fuel structure, etc.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, it is of great research and practical value to have a clear understanding of the soot formation mechanism. The formation process is known as a transition from the gas phase to the condensed phase, involving polycyclic aromatic hydrocarbons (PAHs) formation, nucleation, coagulation, surface growth, and aggregation, , which are influenced by many factors such as temperature, equivalence ratio (or carbon to oxygen (C/O) ratio), , fuel structure, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that the fuel structure had little implications on the critical sooting equivalence ratio with a given number of C–C bonds. However, extensive studies reported that detailed soot characteristics such as soot yield, , size distribution, , and morphology , are affected by fuel structure. Recently, more attention has been shifted to large molecule fuels that are close to practical fuels, yet the results can hardly be analyzed dating back to a specific fuel structure due to the complex molecular configurations and reaction pathways. ,, Meanwhile, it has been revealed that practical fuels would first decompose into small hydrocarbons such as methane, ethane, and ethylene in the combustors or engines. As small hydrocarbons, C2 fuels (ethane, ethylene, and acetylene) have the merits for easy handling in experiments and relatively well-understood gas phase chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations